2013
DOI: 10.1038/nclimate1902
|View full text |Cite
|
Sign up to set email alerts
|

Projections of seasonal patterns in temperature- related deaths for Manhattan, New York

Abstract: Global average temperatures have been rising for the past half-century, and the warming trend has accelerated in recent decades1. Further warming is expected over the next few decades, with significant regional variations. These warming trends will likely result in more frequent, intense and persistent periods of hot temperatures in summer, and generally higher temperatures in winter. Daily death counts in cities increase markedly when temperatures reach levels that are very high relative to what is normal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 26 publications
(54 reference statements)
7
111
0
1
Order By: Relevance
“…Mid-latitude countries typically show a seasonal pattern with a mortality peak in winter [39] and most studies project a reduction of cold-related mortality due to global warming (e.g., [40]), which acts in the opposite direction as the expected increase in future heat-related mortality. Furthermore, some authors also detected an influence of previous winter mortality on summer heat-related mortality [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mid-latitude countries typically show a seasonal pattern with a mortality peak in winter [39] and most studies project a reduction of cold-related mortality due to global warming (e.g., [40]), which acts in the opposite direction as the expected increase in future heat-related mortality. Furthermore, some authors also detected an influence of previous winter mortality on summer heat-related mortality [41].…”
Section: Discussionmentioning
confidence: 99%
“…16 Modeling of future summer and winter climate scenarios for New York City and Europe indicates that the net effect of future warming will be an increase in the number of annual deaths. 17,18 …”
Section: Climate Change Consequences On Healthmentioning
confidence: 99%
“…Elevated mortality in winter is driven largely by respiratory infections and associated cardivascular sequelae. Using a two-day lag of cold temperatures, Li and colleagues projected substantial increases of net annual temperature-related mortality in New York City across a wide range of climate models and scenarios [26]. A few other studies that have quantified both heat- and cold- related mortality found that the increases in heat-related mortality may be offset by decreases in cold-related mortality in some cities [2729].…”
Section: Health Impacts Of Heatmentioning
confidence: 99%